Monitor Efektivitas Pemberian Terapi Antiaritmia pada Pasien dengan Atrial Fibrilasi di IGD RS X Jakarta - Victoria Gloria Andriani Warat; Ni Luh Widani (Lembaga Pengembangan Kinerja Dosen, 2026)
Arrhythmias are generally classified into two groups: disorders of impulse formation and disorders of impulse conduction. Cardiac arrhythmias can also be categorized into three main types: supraventricular arrhythmias, ventricular arrhythmias, and bradyarrhythmias. One of the most commonly encountered arrhythmias in clinical practice is Atrial fibrillation. This study employed a case study method using a nursing process approach. The subjects consisted of two patients: Mrs. S, a 74-year-old female, and Mr. R, a 44-year-old male. The nursing intervention administered was antiarrhythmic therapy using intravenous digoxin. Evaluation was conducted by monitoring the patients’ heart rate and cardiac rhythm using an electrocardiogram (ECG) monitor. The results of the case studies in both patients showed that digoxin therapy produced a positive therapeutic response, as evidenced by a gradual reduction in heart rate. However, ECG monitoring revealed no significant changes in cardiac rhythm. These findings suggest that digoxin is effective for rate control, although it does not restore sinus rhythm.